(3MGTjI eMjj GdOjf GdJGdTj Ydi TQM GdMSGe cGJj Ydi EjSGZhLj aj GdefWbs - (3eMjj GdOjf GdJGdLj, Ch GdJGdTjs
(3ChdgG (B:s
(3bGd GdMeO ddg GdhGLH hLhOg Cbhd GaJJM GdTjN cJGHg HGdMeO HYO GdGHJOG HGdJSejI dCf COG GdhGLH ef TcQ fYeGFg hGLH GdMeO gh GdhUa HGdLejd Ydi LgI GdJYXje hGdJHLjd bUOG (B...s
(3BNQgG (B:s
(3GdEfSGf MjhGf hGdMjhGf LfS jfJL Gf GdEfSGf LfS Ch eDda ef ebOeGJ hgejI cGPHI Cj ZjQ hGbYI hgj bVjI jMce HgG hge GdEfSGf aj CehQ ZjQ eMShSI bjGSG Ydi GdCehQ GdeMShTI JeJ JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf (B1\206s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdadSaI hGdefWbs